2022
DOI: 10.3390/mps5040053
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Intron Evolution

Abstract: Intron evolution may be readily imaged through the combined use of the “dot plot” function of the NCBI BLAST, aligning two sequences at a time, and the Vertebrate “Multiz” alignment and conservation tool of the UCSC Genome Browser. With the NCBI BLAST, an ideal alignment of two highly conserved sequences generates a diagonal straight line in the plot from the lower left corner to the upper right corner. Gaps in this line correspond to non-conserved sections. In addition, the dot plot of the alignment of a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We found that, except for SmCEN -4 and SmTFL -1, each of the genes showed presence of two different genotypes among the cultivars. Screening for variations between the alleles of each gene revealed that most variations fell in intronic regions, while a few resided in the exonic region, which is consistent with the high conservation of protein coding sequence [ 55 ].…”
Section: Discussionmentioning
confidence: 87%
“…We found that, except for SmCEN -4 and SmTFL -1, each of the genes showed presence of two different genotypes among the cultivars. Screening for variations between the alleles of each gene revealed that most variations fell in intronic regions, while a few resided in the exonic region, which is consistent with the high conservation of protein coding sequence [ 55 ].…”
Section: Discussionmentioning
confidence: 87%
“…The analysis of gene structure and intron distribution in protein families may therefore be used to support phylogenetic reconstruction, which otherwise is only based on protein sequence similarities ( Hartung et al 2002 ; Sampedro et al 2005 ; Bockwoldt et al 2019 ). Previously, some vertebrate MC genes have been shown to contain conserved splice sites and intronic sequences ( Calvello et al 2016 , 2019 ; Panaro et al 2020 , 2022 ). In this study, we have investigated the IPs in the transporter domains of human MCs and their orthologs from various species, and analyzed the relationship between the frequent IPs and the specific sequence/structural features of MCs, their sequence similarity, and transport function.…”
Section: Introductionmentioning
confidence: 99%